Diagnostic Phase of Calcium Scoring Scan Applied as the Center of Acquisition Window of Coronary Computed Tomography Angiography Improves Image Quality in Minimal Acquisition Window Scan (Target CTA Mode) Using the Second Generation 320-Row CT. (10th February 2016) - Maeda, Eriko; Yamamoto, Kodai; Kanno, Shigeaki; Ino, Kenji; Tomizawa, Nobuo; Akahane, Masaaki; Torigoe, Rumiko; Ohtomo, Kuni
Abstract : Objective. To compare the image quality of coronary computed tomography angiography (CCTA) acquired under two conditions: 75% fixed as the acquisition window center (Group 75%) and the diagnostic phase for calcium scoring scan as the center (CS; Group CS). Methods. 320-row cardiac CT with a minimal acquisition window (scanned using "Target CTA" mode) was performed on 81 patients. In Group 75% ( n = 40), CS was obtained and reconstructed at 75% and the center of the CCTA acquisition window was set at 75%. In Group CS ( n = 41), CS was obtained at 75% and the diagnostic phase showing minimal artifacts was applied as the center of the CCTA acquisition window. Image quality was evaluated using a four-point scale (4-excellent) and the mean scores were compared between groups. Results. The CCTA scan diagnostic phase occurred significantly earlier in CS (75.7 ± 3.2% vs. 73.6 ± 4.5% for Groups 75% and CS, resp., p = 0.013). The mean Group CS image quality score (3.58 ± 0.63) was also higher than that for Group 75% (3.19 ± 0.66, p < 0.0001). Conclusions. The image quality of CCTA in Target CTA mode was significantly better when the center of acquisition window is adjusted using CS.